Students Positive Response on Semantic Mapping Strategy in English Writing Skill: Respon Positif Siswa terhadap Strategi Semantic Mapping dalam Keterampilan Menulis Bahasa Inggris - Agustina, Ulfa Wulan; Nur, Luluk Choirun Nisak (JEES (Journal of English Educators Society), 2018)
One of the most important skills in English is writing. The writing skill allows the students to express and investigate ideas, thoughts, and beliefs and make them apparent and obvious. Writing encourages writers to think, learn and communicate. Unfortunately, most of the students were difficult and get bored in writing activities. They need some strategies to make easier when they do writing task. Semantic mapping is one of good ways for writing task. It helps students to get idea and improve it into sentences and paragraphs.The purpose of the research is to know whether semantic mapping strategy is able to improve writing skill. This study focuses on students' positive response on semantic mapping strategy in English writing skill. The instrument of this study is using questionnaire which is distributed to the students of second semester in English Department at an Indonesian private university which consisted of 30 students. The result of this study indicates that 25 % of students get easier in learning writing task and 75 % are motivated to have a good writing by using semantic mapping strategy.